2018
DOI: 10.1111/ejss.12548
|View full text |Cite
|
Sign up to set email alerts
|

Determination of quantitative pore‐size distribution of soils with 1H NMR relaxometry

Abstract: Summary The determination of pore‐size distribution (PSD) in soil by conventional methods can be time‐ and effort‐consuming. Therefore, several attempts have been made recently to assess and implement proton nuclear magnetic resonance relaxometry (1H NMR relaxometry) to determine PSDs quantitatively. The 1H NMR relaxometry promises not only to be more time‐ and effort‐saving but also offers a broader range for the estimation of pore size, better resolved results and non‐destructive measurements. To evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 26 publications
2
27
0
1
Order By: Relevance
“…Subject to a later clarification, we will base our work on the definition of Morriss et al (1997) and identify T 2 (1) with clay‐associated water. This is approximately identical to the definition of Meyer et al (2018) of water relaxing faster than 4.5 ms as micro‐ and medium‐pore water. Water fractions relaxing slower are referred to in this scheme as capillary‐pore and macropore water or, in the definition of Meyer et al (2018), as macropore water.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Subject to a later clarification, we will base our work on the definition of Morriss et al (1997) and identify T 2 (1) with clay‐associated water. This is approximately identical to the definition of Meyer et al (2018) of water relaxing faster than 4.5 ms as micro‐ and medium‐pore water. Water fractions relaxing slower are referred to in this scheme as capillary‐pore and macropore water or, in the definition of Meyer et al (2018), as macropore water.…”
Section: Resultssupporting
confidence: 72%
“…This is approximately identical to the definition of Meyer et al (2018) of water relaxing faster than 4.5 ms as micro‐ and medium‐pore water. Water fractions relaxing slower are referred to in this scheme as capillary‐pore and macropore water or, in the definition of Meyer et al (2018), as macropore water. The differentiation between capillary pore and macropore water is arbitrary because the boundaries are not clearly defined.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The direct scaling of NMR relaxation time to pore size was discussed by Jaeger et al (2009), who found better correlation between PSD and T 2 spectra by using a dual-relaxivity model, which defines separate surface relaxivity parameters for micropores and mesopores. Recently, Meyer et al (2018) confirmed this approach by calibration and validation with 14 different soil materials. They found T 2 surface relaxivities of 551.7 and 9.6 mm s -1 for macro-and medium-sized pores defined by matrix potentials of approximately -32 kPa.…”
mentioning
confidence: 89%
“…A CarrPurcell-Meiboom-Gill (CPMG) pulse sequence was used to obtain T2 and the corresponding relaxation rates of the water protons in the samples (Jaeger et al, 2009;Meiboom and Gill, 1958). Pore size distribution was determined following the procedure described in Meyer (2015). The pore size distribution was converted into a water retention curve (matric potential as a function of volumetric water content) using Young-LaPlace equation.…”
Section: Pore Size Distribution and Hydraulic Potential Gradientmentioning
confidence: 99%